Isolation and Identification of Dihydrophenanthrene Derivatives from Dendrobium virgineum with Protective Effects against Hydrogen-Peroxide-Induced Oxidative Stress of Human Retinal Pigment Epithelium ARPE-19 Cells - Pongsawat Panuthai; Rianthong Phumsuay; Chawanphat Muangnoi; Porames Maitreesophone; Virunh Kongkatitham; Wanwimon Mekboonsonglarp; Pornchai Rojsitthisak; Kittisak Likhitwitayawuid; Boonchoo Sritularak (Antioxidants, 2023)
Oxidative stress is a significant factor in the development of age-related macular degeneration (AMD), which results from cell damage, dysfunction, and death in the retinal pigmented epithelium (RPE). The use of natural compounds with antioxidant properties to protect RPE cells from oxidative stress has been explored in Dendrobium, a genus of orchid plants belonging to the family Orchidaceae. Two new compounds and seven known compounds from the MeOH extract of the whole plant of Dendrobium virgineum were successfully isolated and structurally characterized. Out of all the compounds isolated, 2-methoxy-9,10-dihydrophenanthrene-4,5-diol (3) showed the highest protective effect against hydrogen peroxide (H2O2)-induced oxidative stress in human retinal pigment epithelial (ARPE-19) cells. Therefore, it was selected to evaluate its protective effect and mechanism on oxidative-stress-induced ARPE-19 cells. Cells were pre-treated with compound 3 at 25, 50, and 100 µg/mL for 24 h and then induced with 400 µM H2O2 for 1 h. The results demonstrated that compound 3 significantly (p < 0.05) increased cell viability by 10–35%, decreased ROS production by 10–30%, and reduced phosphorylation of p38, ERK1/2, and SAPK/JNK by 20–70% in a dose-dependent manner without toxicity. Furthermore, compound 3 significantly (p < 0.05) modulated the expression of apoptosis pathway proteins (cytochrome c, Bax and Bcl-2) by 20–80%, and enhanced SOD, CAT, and GPX activities, and GSH levels in a dose-dependent manner. These results suggest that compound 3 protects ARPE-19 cells against oxidative stress through MAPKs and apoptosis pathways, including the antioxidant system. Thus, compound 3 could be considered as an antioxidant agent for preventing AMD development by protecting RPE cells from oxidative stress and maintaining the retina. These findings open up new possibilities for the use of natural compounds in the treatment of AMD and other oxidative-stress-related conditions.